Risk factors for facial melasma in women: a case-control study - Handel, A. C. [UNESP]; Lima, P. B. [UNESP]; Tonolli, V. M. [UNESP]; Miot, L. D. B. [UNESP]; Miot, Hélio Amante [UNESP] (Wiley-Blackwell, 2014)
Background Melasma is a localized chronic acquired hypermelanosis, common in adult women and which has an important impact on their life quality. Its pathology is unknown, despite some recognized triggering factors.Objective To evaluate risk factors for developing facial melasma in women.Methods This was a case-control study involving adult women with or without facial melasma, paired by age. Variables were grouped into hierarchical levels: personal characteristic data, exposure variables, links to hormonal stimuli and the State-Trait Anxiety Inventory questionnaire, Brazilian version. The data were analysed using conditional multiple logistic regression.Results We evaluated 207 patients and 207 controls. The mean age was 38 years. Cases differed from controls for phototype, Amerindian ancestry [odds ratio (OR) 2.59], years of beach or rural residence (OR 1.06), time exposed to sun at work (OR 1.65), time exposed to sun in leisure activities (OR 1.04), antidepressant/anxiolytic use (OR 4.96), menstrual irregularity (OR 3.83), pregnancy history (OR 3.59), years of oral contraceptive use (OR 1.23) and anxiety scores (OR 1.08). A family history of melasma was reported in 61% of cases and 13% of controls (OR 10.40).Conclusions Facial melasma is independently associated with elements linked to pigmentation capacity, family ancestry, chronic sun exposure, sexual hormone stimuli, psychotropics and anxiety traits.